2017
DOI: 10.1161/circimaging.117.006843
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Features Are Superior to Conventional Quantitative Computed Tomographic Metrics to Identify Coronary Plaques With Napkin-Ring Sign

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 33 publications
0
125
0
4
Order By: Relevance
“…In recent years, Radiomics has been applied to many health- investigations, such as identifying the coronary plaques [33]. In neurology, it is widely applicable for detecting Alzheimer's disease [34] and Parkinson's disease [35].…”
Section: Applicationsmentioning
confidence: 99%
“…In recent years, Radiomics has been applied to many health- investigations, such as identifying the coronary plaques [33]. In neurology, it is widely applicable for detecting Alzheimer's disease [34] and Parkinson's disease [35].…”
Section: Applicationsmentioning
confidence: 99%
“…Feature extraction, reduction and model construction were performed on R software, which is a free and open-source tool. 22 SPSS (version 17.0) was used for the correlation tests.…”
Section: Discussionmentioning
confidence: 99%
“…This result was strongly consistent with those of previous studies. 22,26,27 Among all the 10 features, most of them were higherorder statistics features and utilised wavelet transform. Higher-order statistics features could display subtle alterations in tissue morphology more explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous radiomics studies showed that the quantitative radiomic features could represent the changes in pathology and gene level, and thus had encouraging performance in cancer diagnosis, treatment outcome prediction, and prognosis prediction [20][21][22][23]. Besides application in cancer, radiomics has also been used in the heart diseases, such as hypertrophic cardiomyopathy [24] and coronary heart disease [25]. Furthermore, it has also been applied to differentiate primary progressive pulmonary tuberculosis from community-acquired pneumonia in children [26].…”
Section: Introductionmentioning
confidence: 99%